2017
DOI: 10.1016/j.ijid.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Changes in eosinophil count during bacterial infection: revisiting an old marker to assess the efficacy of antimicrobial therapy

Abstract: The eosinophil count appears to normalize faster than C-reactive protein (CRP) and polymorphonuclear neutrophils in eosinopenic patients on appropriate antimicrobial therapy. This simple test is easy to perform as part of a regular complete blood count, with no additional costs as required for CRP or procalcitonin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 22 publications
3
33
0
1
Order By: Relevance
“…Similar to previous results [14,[16][17][18], we found a sustained eosinopenic response in nonsurvivors, while the median eosinophil count in survivors tended to quickly rise to normal levels within days. The value of eosinophil count in predicting response to antibiotic therapy was recently reported [20]. However, significant overlap of EC was noted between survivors and non-survivors in our study and persistent eosinopenia for several days was not uncommon in survivors (e.g.…”
Section: Ec As a Monitoring Parametersupporting
confidence: 38%
See 1 more Smart Citation
“…Similar to previous results [14,[16][17][18], we found a sustained eosinopenic response in nonsurvivors, while the median eosinophil count in survivors tended to quickly rise to normal levels within days. The value of eosinophil count in predicting response to antibiotic therapy was recently reported [20]. However, significant overlap of EC was noted between survivors and non-survivors in our study and persistent eosinopenia for several days was not uncommon in survivors (e.g.…”
Section: Ec As a Monitoring Parametersupporting
confidence: 38%
“…Similarly, Terradas et al [17] found that sustained eosinopenia (< 45/µL) in patients with bacteremia was an independent risk factor for mortality, while in survivors' eosinophil counts tend to return to normal levels within 2-3 days. More recently monitoring the eosinophil count has been suggested as a marker of efficacy of antibiotic therapy [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Nonclinical data support that eosinophils may be activated by, and have the ability to kill, certain bacteria, and eosinopenia has been described as a feature of modeled, acute bacterial infections [5,97,98]. In patients, an inverse relationship between bacterial load and peripheral blood eosinophils has been reported [99,100], and eosinopenia may predict a bacterial etiology for patients with sepsis [101]. Eosinophil degranulation products have been detected in respiratory secretions from patients during respiratory syncytial viral (RSV) infections [102], and eosinophil degranulation was associated with a more favorable outcome in mice infected with pneumonia virus of mice (PVM), a respiratory virus infection in mice similar to human RSV [103].…”
Section: Viral and Microbial Infectionmentioning
confidence: 99%
“…Several studies evaluated the behaviour of eosinophils during acute bacterial infections, where eosinopenia has been shown to be a common feature [ 17 ]. During bacteremia, there is an inverse relationship between bacterial load and peripheral blood eosinophils [ 123 ] and eosinopenia was shown to be a reliable marker of bacterial aetiology in patients admitted with sepsis to the intensive care unit [ 124 126 ]. Finally, low eosinophil count was shown to be a risk factor for persistent diarrhoea or death and recurrent disease in patients with Clostridium difficile infection [ 127 ].…”
Section: Eosinophils In Infectious Diseasesmentioning
confidence: 99%